(a + b - c)(a + b + c)

Question

Asked 11/18/2014 6:31:45 AM

Updated 11/18/2014 7:51:05 AM

7 Answers/Comments

This conversation has been flagged as incorrect.

s

= 25/3 - 11/6;

= 50/6 - 11/6;

= 39/6;

= 13/2;

= 6 1/2

neolinkjay|Points 15|

neolinkjay|Points 15|

6x - 12 = 4;

6x = 4 + 12;

6x = 16;

x = 16/6;

x = 8/3

andrewpallarca|Points 45900|

6x - 12 = 4;

6x = 4 + 12;

6x = 16;

x = 16/6;

x = 8/3

Lally Grenio|Points 10|

IAmSoLame|Points 690|

neolinkjay|Points 15|

= 25/3 - 11/6;

= 50/6 - 11/6;

= 39/6;

= 13/2;

= 6 1/2

Question

Asked 11/18/2014 6:31:45 AM

Updated 11/18/2014 7:51:05 AM

7 Answers/Comments

This conversation has been flagged as incorrect.

Rating

8

(ax - by)(ax + by) = a^2x^2 - b^2y^2

Added 11/18/2014 7:33:48 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [11/18/2014 7:42:11 AM]

8

(2x - y)(4x^2 + 2xy + y^2)

= (2x)^3 - y^3

= 8x^3 - y^3

= (2x)^3 - y^3

= 8x^3 - y^3

Added 11/18/2014 7:34:59 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [11/18/2014 7:42:35 AM]

8

(a + b - c)(a + b + c)

= a^2 + ab + ac + ab + b^2 + bc - ac - bc - c^2

= a^2 + b^2 - c^2 + 2ab

= a^2 + ab + ac + ab + b^2 + bc - ac - bc - c^2

= a^2 + b^2 - c^2 + 2ab

Added 11/18/2014 7:39:42 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [11/18/2014 7:43:34 AM]

8

(b^2 + 8 )(b^2 - 8) = b^4 - 64

Added 11/18/2014 7:40:47 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [11/18/2014 7:43:44 AM]

8

(yx - 5)( yx + 5) = y^2x^2 - 25

Added 11/18/2014 7:41:17 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [11/18/2014 7:44:05 AM]

8

(4a + x)(a - x)

= 4a^2 - 4ax + ax - x^2

= 4a^2 - 3ax - x^2

= 4a^2 - 4ax + ax - x^2

= 4a^2 - 3ax - x^2

Added 11/18/2014 7:46:44 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [11/18/2014 7:52:07 AM]

8

(x + 2)(x - 2) = x^2 - 4

Added 11/18/2014 7:51:05 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [11/18/2014 8:02:35 AM]

2-x = 16 User: solve 2x = 1/32 User: Solve 49 x = 7

Question

Updated 11/18/2014 7:32:15 AM

3 Answers/Comments

2 - x = 16;

2 - 16 = x;

x = -14

2 - 16 = x;

x = -14

Added 11/18/2014 7:24:46 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [11/18/2014 7:30:38 AM]

2x = 1/32;

x = 1/32 ÷ 2;

x = 1/32 * 1/2;

x = 1/64

x = 1/32 ÷ 2;

x = 1/32 * 1/2;

x = 1/64

Added 11/18/2014 7:25:24 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [11/18/2014 7:31:02 AM]

34,468,870

questions answered

S

L

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

P

1

L

P

1

Points 837 [Total 6710] Ratings 19 Comments 647 Invitations 0 Offline

There are no comments.